Antiviral Drugs: Mechanisms of Actions and Viral Resistance - Hakim, Hakimullah (Journal of Natural Sciences – Kabul University, 2021)
Currently, as the COVID-19 pandemic continues to spread throughout the world, with over 104 million confirmed cases and more than 2.2 million lives lost as of February 6, 2021, the production and application of antiviral drugs for the treatment of viral diseases have become more critical than ever. Although various countries are using different antiviral drugs for the treatment of COVID-19 patients, none of these drugs have been certified by the World Health Organization as effective. This review article aims to provide an overview of the application of antiviral drugs, their mechanisms of action, and how viruses develop resistance against them.